The Effect of Contextual Teaching and Learning Model on Students’ Critical Thinking Skills in Class V Science and Technology Subjects - Mustamiroh Mustamiroh; Nur Isnania; Tri Wahyuningsih; Iksam Iksam; Ramli Buhari (Edumaspul: Jurnal Pendidikan, 2025)
This study is based on the lack of critical thinking skills of class V students of SDN 004 Samarinda Ilir. One of the skills needed by students is the ability to think critically in learning. However, the learning model in schools that is less varied is still often applied by teachers, so that students' abilities are not optimally developed, especially in the subject of science and natural sciences. The purpose of this study was to determine the effect of the Contextual Teaching and Learning (CTL) learning model on students' critical thinking skills in the subject of science and natural sciences of Class V SDN 004 Samarinda Ilir in the 2024/2025 academic year. This type of research uses a quantitative method with an experimental research type. The design used is Quasi Experimental with the Nonequivalent Control Group Design model. The study population consisted of all class V students of SDN 004 Samarinda Ilir, with a sample size of 56 people divided into control classes and experimental classes. The instruments used included 16 multiple-choice questions as test instruments, as well as documentation of learning activities as non-test instruments. The data analysis techniques applied include normality test, homogeneity test, and hypothesis test with Independent Sample t-test, because the research data is normally distributed and homogeneous, and N-Gain Test. The results of the hypothesis test research using the Independent Sample t-test showed a Sig. (2-tailed) value of 0.000 for the experimental and control classes. Based on the Independent Sample t-test decision-making criteria, if the Sig. (2-tailed) value <0.05 then H0 is rejected and H1 is accepted, so there is an influence of the Contextual Teaching and Learning (CTL) learning model on students' critical thinking skills in the science subject of class V SDN 004 Samarinda Ilir in the 2024/2025 academic year. The increase in critical thinking skills in the experimental group was 0.36 and was included in the moderate category.